Learning styles and academic achievement in students of the first cycle of the Master’s Program in Educational Sciences majoring in Teaching English as a Foreign Language at the National University of Education Enrique Guzman y Valle, La Molina, Lima, 2016 - Jalixto Erazo, Hans Manuel (2017)
This study known as Learning styles and academic achievement in students of the first cycle of the Master’s Program in Educational Sciences majoring in Teaching English as a Foreign Language at the National University of Education Enrique Guzman y Valle, La Molina, Lima, 2016, aims to determine the degree of relationship between variables learning styles and academic achievement. It has been run a research of substantive type, correlational design with descriptive method and a non-probabilistic sample. The population was of 27 students of the first cycle of the Master’s Program in Educational Sciences majoring in Teaching English as a Foreign Language. All the students were involved in the research, the sample was the same as the population and thus a census context was reported. In addition, we have validated research instruments to then apply them. Finally, hypothesis testing has proved that learning styles have a significant relationship with academic achievement in students of the first cycle of the Master’s Program in Educational Sciences majoring Teaching English as a Foreign Language at the National University of Education Enrique Guzman y Valle, La Molina, Lima, 2016, because it has been observed that learning styles are directly related to academic achievement. That is, at higher levels of learning styles, there will be a higher level of learning achievement, and according to Spearman’s correlation of 0,541, this represents a mean positive correlation.